Variations in the care of agitated patients in Australia and New Zealand ambulance services. (15th December 2019) - Nambiar, Dhanya; Pearce, James W; Bray, Janet; Stephenson, Michael; Nehme, Ziad; Masters, Stacey; Brink, Deon; Smith, Karen; Arendts, Glenn; Fatovich, Daniel; Bernard, Stephen; Haskins, Brian; et al.
Abstract: Objective: The objective of the present study is to examine variations in paramedic care of the agitated patient, including verbal de‐escalation, physical restraint and sedation, provided by ambulance services in Australia and New Zealand. Methods: To examine the care of agitated patients, we first identified and reviewed all clinical practice guidelines for the management of agitated patients in Australian and New Zealand ambulance services between September and November 2018. We then conducted a structured questionnaire to obtain further information on the training, assessment and care of agitated patients by the ambulance services. Two authors extracted the data independently, and all interpretations and results were reviewed and confirmed by relevant ambulance services. Results: There were 10 independent clinical practice guidelines for the care of agitated patients in the 10 ambulance services. All services reported training in the management of agitated patients, and two services used a validated tool to assess the level of agitation. All services used physical restraint, although six services required police presence to restrain the patient. All ambulance services used some form of sedation, typically divided into the management of mild to moderate, and severe agitation. The most common agent for sedation was midazolam, while ketamine was the most common agent for sedating severely agitated patients. The maximum dose was varied, and contraindications for sedating agents varied between services. Conclusions: There were wide variations across the ambulance services in terms of the assessment of agitation, as well as the use of physical restraint and sedation.